Increasing the usability of climate science in political decision-making - Emily R. Newsom; Andrea J. Fassbender; Ashley E. Maloney; Seth M. Bushinsky (Elementa: Science of the Anthropocene, 2016)
Abstract As climate-science graduate students at the University of Washington, we had the opportunity to engage in a political process focused on implementing legislation to reduce greenhouse gas emissions in Washington State. Our insights gained from this rare, first-hand, experience may be particularly relevant to other climate scientists. We argue that inflexible research goals within the United States climate-science community limit the relevance of the knowledge our community creates. The mismatch between climate-science research and the information needs of policy makers, while widely acknowledged in certain domains, has yet to be fully appreciated within many earth science disciplines. Broadening the climate-science training of graduate students to include education on the uses of climate information outside of academic settings would both inform and motivate new research directions, and engender validation of non-traditional research within disciplinary cultures.